2021
DOI: 10.1097/ncc.0000000000001040
|View full text |Cite
|
Sign up to set email alerts
|

Information Provision, Decision Self-efficacy, and Decisional Conflict in Adopting Health Behaviors Among Patients Treated for Colorectal Cancer

Abstract: BackgroundHealth promotion is necessary to mitigate the negative consequences of colorectal cancer and its treatment. Rates of behavior modification are low in populations of cancer patients. Studies are needed to determine the factors, such as decisional conflict, which influence adoption of healthy behaviors following a cancer diagnosis.ObjectiveTo examine the effects of information provision, decision self-efficacy, and decisional conflict on the adoption of healthy behaviors among patients with colorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…On the other hand, survivors with higher self-efficacy are more likely to engage in self-management and take appropriate actions to promote health and improve QoL [42]. Our results were consistent with Lee et al They found that providing enough additional information to improve self-efficacy could promote healthy lifestyles, thereby improving QoL [43]. However, there are few studies on the impact of self-efficacy on QoL in CRC survivors.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, survivors with higher self-efficacy are more likely to engage in self-management and take appropriate actions to promote health and improve QoL [42]. Our results were consistent with Lee et al They found that providing enough additional information to improve self-efficacy could promote healthy lifestyles, thereby improving QoL [43]. However, there are few studies on the impact of self-efficacy on QoL in CRC survivors.…”
Section: Discussionsupporting
confidence: 90%
“…It is assumed that patients are not sufficiently knowledgeable and make decisions under undue pressure from others, regardless of their values and preferences. In this case, it can lead to a high degree of decisional conflict or uncertainty about which treatment to choose (Lee & Bryant-Lukosius, 2021). In a recent study by Shun et al, (2018), HCC patients reported moderate uncertainty about treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Decision self-efficacy is a belief in one's ability to make decisions, including participating in SDM (O'Connor, 2002).Individuals with higher decision self-efficacy have lower decisional conflict. They are more confident that they have enough information, feel supported, and make the best choices for themselves (Lee & Bryant-Lukosius, 2021). Providing information is associated with greater decision self-efficacy, which can significantly reduce decisional conflict (Gao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%